Establishing Commonality Versus Affirming Distinctiveness: Patterns of Personality Judgments in China and the United States. (May 2014) - Locke, Kenneth D.; Zheng, Dianhan; Smith, Juliane
We predicted that members of Chinese groups would tend to express personality judgments that establish commonalities among members, whereas members of American groups would tend to express judgments that affirm how members differ. We had groups of five acquaintances (23 groups at one U.S. university, 28 groups at three Chinese universities) rate their own and each other's traits and subjected the round-robin data to social relations model and social accuracy model analyses. As hypothesized, Chinese were more likely to portray their peers as similar to themselves and to each other as indicated by greater perceived self-other similarity and less variance in target ratings; conversely, Americans were more likely to express a shared understanding of what distinguished each group member from others, as indicated by greater distinctive agreement and target variance (consensus). Collectivistic values mediated effects of country on perceived similarity; individualistic values mediated effects of country on consensus and perceived similarity.